Assessing green finance and technological innovation's contribution to carbon emission reduction in mineral-based economies of the belt and road initiative - Xiaoli Liao; Mengye Sun; Yali Pham (Energy Strategy Reviews)
This study examines the influence of institutional performance, green finance, and technology on environmental performance in mineral-based nations involved in the Belt and Road Initiative (BRI), focusing on the period of economic growth from 1991 to 2019. The use of the STIRPAT model, along with spatial econometric methods, yields noteworthy results in the analysis. The adoption of renewable energy leads to a 12 % decrease in CO₂ emissions among the countries studied, underscoring its crucial importance for environmental sustainability. Enhancements in institutional quality indicate a 14 % increase in ecological efficiency, whereas a rise in government spending on renewable energy is associated with a 10 % boost in the utilization of green finance and promoting environmental conservation. Nonetheless, financial development shows a varied impact, highlighting the need for policy measures to align growth with sustainability. The findings highlight the essential importance of customized policies and strong institutional structures when tackling environmental issues. This study not only addresses a gap in understanding the interplay of these variables but also provides practical insights for policymakers to promote sustainable development. The results hold considerable importance for reaching sustainable environmental goals and improving cooperation among BRI countries.